PERAN IBNU MUQLAH DALAM PENGEMBANGAN ILMU KALIGRAFI - Siti Rahimah Harahap (Yayasan Haiah Nusratul Islam, 2025)
Calligraphy holds a significant role in Islamic tradition, not only as a visual art form but also as a medium to convey religious, aesthetic, and philosophical messages. This study focuses on the contributions of Ibn Muqlah, a pivotal figure in the history of Islamic calligraphy, particularly through the development of the theory of al-Khaṭṭ al-Manṣūb. This theory bases the art of calligraphy on geometric proportions, creating visual harmony while reflecting Islamic spiritual values. The research employs a descriptive-qualitative approach through literature review, document analysis, and visual observation of calligraphic works. The findings indicate that the al-Khaṭṭ al-Manṣūb theory not only revolutionized calligraphy in its time but also became a foundation for the development of various script styles, such as naskhī and ṯuluth. Ibn Muqlah's contributions extend to the modern era, influencing both traditional art and digital applications. Moreover, calligraphy serves not only as an expression of aesthetics but also as a medium for disseminating religious values and Islamic cultural identity. This study provides new insights into the integration of art, spirituality, and culture in Islamic tradition and highlights the relevance of Ibn Muqlah's theory in contemporary art